Evaluating mobility management models for content forwarding in named data networking environments - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Abdulkadir, H Alkali; Midi, Nur Shahida; Abd. Rahman, Faridah (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Named Data Networking (NDN) performs its routing and forwarding decisions using name prefixes. This removes some of the issues affecting addresses in our traditional IP architecture such as limitation in address allocation and management, and even NAT translations etcetera. Another positivity of NDN is its ability to use the conventional routing like the link state and distance vector algorithm. In route announcement, NDN node broadcasts its name prefix which consists of the knowledge of the next communicating node. In this paper, we evaluate the performance of mobility management models used in forwarding NDN contents to a next hop. This makes it crucial to select an approach of mobility model that translates the nature of movement of the NDN mobile routers. A detailed analysis of the famous mobility model such as the Random Waypoint mobility and Constant Velocity were computed to determine the mobility rate of the NDN mobile router. Simulation analysis was carried out using ndnSIM 2.1 on Linux Version 16.1. we build and compile with modules and libraries in NS-3.29. The sample of movement of the mobile router is illustrated and our result present the viability of the Constant Velocity model as compared with the Random Way point. Keywords—Named Data Networking, Prefix, Broadcast, ndnSIM, NS-3.29